A Task Inventory at Job-Entry Level for Malaysian Bakers - Kuroda, Masako (1996)
As Malaysia strides towards achieving its Vision 2020 to become an industrialised nation, there is need and demand for more capable, skilled and semiskilled workers. It has been the contention that what is taught in vocational schools do not meet the current needs of the industry; that there is a necessity for closer linkages between industry and vocational education. So it is necessary to get the employers and the job incumbents to be involved in vocational Home Economics related programmes, particularly the Bakery and Confectionery programme. A study is needed to examine the relationship between programme content and the competencies required by the industries in which the students are being trained for, especially in Home Economics because the market demand is comparatively small. In this study the task inventory analysis technique was used. The decision rule whether to accept or reject the tasks required for job entry-level, was based on the mean score of 2.0 on scale of I-3 for frequency of performance as well as level of importance. Analysis of the data indicated that all the tasks under duty statements, General Duties and Specific Duties, were accepted as job-entry tasks for a baker. As such these tasks were considered relevant for a task inventory which could be utilised as a guide for the training of vocational education students of the Bakery and Confectionery programme in the country. However, there were differences in the ranking of tasks, on how frequently they were performed or how important the tasks were - at job entry-level, among bakers, employers, teachers and students. The responses of each group differed based on their perception of the tasks carried out. Developing an inventory of tasks for bakers at job-entry provided the linkage between industry and vocational education through the involvement of the employers and bakers. Teachers and students in the vocational Home Economics programmes were made aware of the required competencies at job-entry level.